2012
DOI: 10.1016/j.jvs.2012.01.068
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of femoral vein transposition for autogenous arteriovenous hemodialysis access

Abstract: Femoral vein transposition in the lower limb is a valuable alternative to arteriovenous grafts in terms of infection and long-term patency. Secondary venous percutaneous angioplasties may be necessary. High flow rates are frequently observed and patient selection is essential to avoid ischemic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 16 publications
1
51
0
4
Order By: Relevance
“…Rueda et al (16) reported 10 patients with tFV LE-AVF accesses, and none had a lower extremity ischemic event. Bourquelot et al (17) reported secondary patency rates at 1 and 9 years of 84% 65% and 56%69%, respectively, in 72 tFV created in 70 patients. A major concern encountered in these studies was infection at femoral vein harvest site and compartment syndrome, especially in patients with low ankle-brachial index, highlighting the importance of patient selection.…”
Section: Transposed Femoral Vein Le-avfmentioning
confidence: 98%
“…Rueda et al (16) reported 10 patients with tFV LE-AVF accesses, and none had a lower extremity ischemic event. Bourquelot et al (17) reported secondary patency rates at 1 and 9 years of 84% 65% and 56%69%, respectively, in 72 tFV created in 70 patients. A major concern encountered in these studies was infection at femoral vein harvest site and compartment syndrome, especially in patients with low ankle-brachial index, highlighting the importance of patient selection.…”
Section: Transposed Femoral Vein Le-avfmentioning
confidence: 98%
“…4 However, prosthetic grafts are frequently complicated by infection and venous anastomosis stenosis. Access loss as a result of infection is far more common in all thigh grafts compared with autologous thigh AV access (18.40% vs 1.61%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…3 (91%/45%) and secondary (84%/56%) patency, respectively, in a series of 72 tFV cases. 4 Similar to tFV, the described sPG technique does not involve a venovenous anastomosis, which is the most common site for restenosis. A major advantage of sPG, however, is that it allows for the conversion of a long thin conduit into a shorter but larger-diameter autologous conduit without disruption of the deep venous circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Bourquelot et al 24 published long-term follow-up data for 70 patients with surgically created femoral fistulae. These lower limb fistulae had higher flow than upper limb fistulae with a mean flow of 1529±429 mL/min (range, 700-3000 mL/min) and are substantially larger in diameter than the current ROX stent anastomosis, which has a 4-mm diameter and admits 800 to 1000/min.…”
Section: Potential Procedural Complicationsmentioning
confidence: 99%
“…Thirteen patients (18%) required fistula ligation: 5 diabetic patients with peripheral arterial occlusive disease and high flow fistulae developed ischemic complications (1 major amputation included); 1 patient developed lower leg compartment syndrome (acute, required fasciotomies); 2 acute venous hypertension; 2 secondary major edema; 1 high-output cardiac failure (9 years after fistula creation, high-flow fistula); 2 major bleeding. 24 The group now excludes patients with diabetes mellitus and patients…”
Section: Potential Procedural Complicationsmentioning
confidence: 99%